Design and Synthesis of New Pyrimidine-Quinolone Hybrids as Novel hLDHA Inhibitors - Iván Díaz; Sofia Salido; Manuel Nogueras; Justo Cobo (Pharmaceuticals, 2022)
A battery of novel pyrimidine-quinolone hybrids was designed by docking scaffold replacement as lactate dehydrogenase A (hLDHA) inhibitors. Structures with different linkers between the pyrimidine and quinolone scaffolds (10-21 and 24–31) were studied in silico, and those with the 2-aminophenylsulfide (U-shaped) and 4-aminophenylsulfide linkers (24–31) were finally selected. These new pyrimidine-quinolone hybrids (24–31)(a–c) were easily synthesized in good to excellent yields by a green catalyst-free microwave-assisted aromatic nucleophilic substitution reaction between 3-(((2/4-aminophenyl)thio)methyl)quinolin-2(1H)-ones 22/23(a–c) and 4-aryl-2-chloropyrimidines (1–4). The inhibitory activity against hLDHA of the synthesized hybrids was evaluated, resulting IC50 values of the U-shaped hybrids 24–27(a–c) much better than the ones of the 1,4-linked hybrids 28–31(a–c). From these results, a preliminary structure–activity relationship (SAR) was established, which enabled the design of novel 1,3-linked pyrimidine-quinolone hybrids (33–36)(a–c). Compounds 35(a–c), the most promising ones, were synthesized and evaluated, fitting the experimental results with the predictions from docking analysis. In this way, we obtained novel pyrimidine-quinolone hybrids (25a, 25b, and 35a) with good IC50 values (<20 μM) and developed a preliminary SAR.